PENGARUH LINGKUNGAN SOSIAL DALAM PENDIDIKAN PERSPEKTIF HADIS NABI - Nur Hafisah; Rabea Rahakbaw; Rusyaid Rusyaid (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
Education has an important role in shaping individual character and personality, where social environments such as friends, parents, and educators make significant contributions. This study aims to analyse the influence of the social environment on student education based on the hadith perspective. The method used is literature study, by collecting data from various relevant literatures. The results showed that positive interactions in the social environment can increase students' learning motivation and academic achievement. Peers serve as encouraging support, while parents and educators serve as mentors who shape moral and ethical values. The study concludes that collaboration between parents, educators and peers is essential to create an educational ecosystem that not only focuses on academic achievement, but also on developing students' character. By integrating islamic values into education, it is expected that the resulting generation will not only be intellectually smart, but also rich in morals and ethics. This research provides new insights into the importance of a holistic approach in education to address the challenges students face.